Mining the Literature: Assessing the Science of Milk Fat Globule Membrane and Its Components Utilizing Comprehensive Literature Search Techniques. (29th May 2020) - Brink, Lauren; Walsh, Kelly; Shah, Neil; Patterson, Ashley
Abstract: Objectives: Milk fat globule membrane (MFGM) is the component of milk responsible for fat delivery. MFGM is a single component but contains a variety of glycosylated proteins and lipids that influence health. The objective herein is to highlight the breadth of research surrounding MFGM and its individual components. Methods: Searches on MFGM and its components (individual proteins, lipids, and carbohydrates) were conducted August 2019 in Embase. For the 'MFGM' search we added specific exclusion terms to focus results around nutrition. The individual components were searched for in combination with 'AND Milk'. Downloaded publications were loaded into R (version 3.6.1) for merging, filtering and categorization. MFGM and individual component searches were combined into one data frame while ensuring no duplicates. Once searches were merged, publication abstracts and titles were searched for keywords associated with study type (Clinical, Preclinical or Analytical) and functional benefit area. Finally, pediatric intervention trials were identified and summarized. Results: Over 2150 scientific journal articles have been published on the topic of MFGM and its components since 1950. This includes analytical research characterizing MFGM structure and components, preclinical publications demonstrating mechanisms of action as well as human intervention trials. Within the Clinical and Preclinical studies, 1169 papers were categorized with Brain (36%), Gut (30%) or Immune (3%) as the predominant benefit area. Within pediatric intervention trials, over 1800 infants have been studied, with interventions lasting up to 12 months for a combined study intervention period of at least 424 weeks and follow-up measures taken up to 6 years following study initiation. Conclusions: The growing body of literature on MFGM reflects the importance of this naturally occurring compound with multiple health benefits. Funding Sources: All of the authors are employed by RB.